2019
DOI: 10.1177/0959683619831432
|View full text |Cite
|
Sign up to set email alerts
|

Optical dating of Holocene paleosol development and climate changes in the Yili Basin, arid central Asia

Abstract: Optically stimulated luminescence (OSL) dating was conducted on the K-feldspar and quartz fractions of a Holocene loess-paleosol sequence in the Yili Basin, in the core area of arid central Asia (ACA). Age overestimation using the post-IR IR (pIR50IR170) signals from feldspar was observed for paleosols, because of poor bleaching prior to deposition. Therefore, a reliable age framework for the studied section was established using OSL dating of coarse-grained quartz, combined with a Bacon age model. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 74 publications
0
17
0
2
Order By: Relevance
“…Because of the lack of suitable organic materials such as plant remains and charcoal, contamination by modern carbon, and/or the redeposition of old carbon, many uncertainties remain about the use of the bulk organic matter content of loess for 14 C dating (Hatté, Pessenda, et al, ; Li et al, ; Pessenda et al, ). Many recent studies have suggested that since OSL dating can determine the ages of eolian deposits by directly measuring the deposition ages of minerals (such as quartz and feldspar), it may be more suitable for providing a reliable absolute chronology for loess sections in ACA (e.g., Chongyi et al, ; Li et al, ; Song et al, ; Song et al, ; Wang, Jia, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lack of suitable organic materials such as plant remains and charcoal, contamination by modern carbon, and/or the redeposition of old carbon, many uncertainties remain about the use of the bulk organic matter content of loess for 14 C dating (Hatté, Pessenda, et al, ; Li et al, ; Pessenda et al, ). Many recent studies have suggested that since OSL dating can determine the ages of eolian deposits by directly measuring the deposition ages of minerals (such as quartz and feldspar), it may be more suitable for providing a reliable absolute chronology for loess sections in ACA (e.g., Chongyi et al, ; Li et al, ; Song et al, ; Song et al, ; Wang, Jia, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Loess is extensively distributed, continuously deposited, and of large thickness, and it has played a key role in reconstructing the paleoclimatic evolution of terrestrial environments on orbital and suborbital timescales (Lauer et al, ; Liu, ; Wang et al, ). In the past several decades, in order to reconstruct the paleoclimatic evolution of ACA, multiproxy studies of loess deposits on both orbital and suborbital timescales have been conducted in Xinjiang (eastern ACA; e.g., Chen et al, ; Gao et al, ; Wang, Jia, et al, 2019), Tajikistan (e.g., Ding, Ranov, et al, ; Jia, Lu, et al, ; Yang et al, ), and Kazakhstan (Ran & Feng, ) in the central part of ACA. Most of these studies show that the climate variations are in‐phase with those of monsoonal Asia on orbital timescales and out‐of‐phase on suborbital timescales.…”
Section: Introductionmentioning
confidence: 99%
“…To make it suitable to date even younger samples (e.g., of hundreds of years), the second IR stimulation was decreased to 150 • C, with a preheat treatment at 180 • C [28,56]. In several studies, the second IR stimulation temperature was changed to 170 • C with the preheat temperature at 200 • C to date Holocene aeolian deposits [57][58][59].…”
Section: Two-step Ir Stimulationmentioning
confidence: 99%
“…天山北麓年均降水量由高山区的大于500 mm减少 到盆地中心的不足100 mm, 属大陆性干旱、半干旱气 候 [13] . 降雨主要集中在春夏两季, 盛行风以西风为主 导 [30] . 这里发育了包括安集海河在内的一系列的河流 [21] , 识别晒退充分的石英颗粒需要测量获 取大量的数据进行统计分析, 因此, 本研究采用改进的 光释光测年技术, 可快捷高效地获取大量年轻石英颗 粒的等效剂量 [22] .…”
Section: 研究区域概况unclassified
“…这里发育了包括安集海河在内的一系列的河流 [21] , 识别晒退充分的石英颗粒需要测量获 取大量的数据进行统计分析, 因此, 本研究采用改进的 光释光测年技术, 可快捷高效地获取大量年轻石英颗 粒的等效剂量 [22] . 该方法的可靠性已在其他地点得到 验证 [30] . [22] .…”
Section: 研究区域概况unclassified